Moderation Based Learning in Islamic Religious Education - Dewi Purnamasari (International Journal of Islamic Educational Research, 2026)
Islamic Religious Education (PAI) learning has a strategic role in shaping the character of students who are religious, tolerant, and have noble morals. Amidst the reality of Indonesian multicultural society, PAI learning is required to be able to internalize the values of religious moderation as an effort to prevent extreme, radical, and intolerant attitudes. Religious moderation is an important paradigm in Islamic education to instill a balanced and contextual religious attitude. This proceedings article aims to examine the concept, strategy, and implications of moderation-based Islamic Religious Education learning through the Systematic Literature Review (SLR) approach. The SLR method is used to examine journal articles, scientific books, and proceedings relevant to the topic of PAI learning and religious moderation in the last ten years. The results of the study indicate that moderation-based PAI learning is based on the values of wasathiyah, tawazun, i'tidal, and tasamuh which are integrated into the curriculum, learning methods, and the role models of educators. The implementation of moderation-based PAI learning has a positive impact on the formation of inclusive, tolerant attitudes and the ability to live peacefully together in students. This article is expected to be an academic reference for educators and researchers in developing Islamic Religious Education learning that is relevant to the social challenges and diversity of Indonesian society.